Evaluating point and density forecasts of DSGE models - Maik H. Wolters (Kiel University, Department of Economics, 2013)
This paper investigates the accuracy of forecasts from four DSGE models for inflation, output growth and the federal funds rate using a real-time dataset synchronized with the Fed's Greenbook projections. Conditioning the model forecasts on the Greenbook nowcasts leads to forecasts that are as accurate as the Greenbook projections for output growth and the federal funds rate. Only for inflation the model forecasts are dominated by the Greenbook projections. A comparison with forecasts from Bayesian VARs shows that the economic structure of the DSGE models which is useful for the interpretation of forecasts does not lower the accuracy of forecasts. Combining forecasts of several DSGE models increases precision in comparison to individual model forecasts. Comparing density forecasts with the actual distribution of observations shows that DSGE models overestimate uncertainty around point forecasts.
urn:nbn:de:hebis:30:3-347120
Keywords: C53; E31; E32; E37; 330; DSGE models; Bayesian VAR; forecasting; model uncertainty; forecast combination; density forecasts; real-time data; Greenbook